2019
DOI: 10.1002/aenm.201900891
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Machine Learning Techniques for Predicting the Efficiency of Fullerene Derivatives‐Based Ternary Organic Solar Cells at Ternary Blend Design

Abstract: Ternary organic solar cells (OSCs) have progressed significantly in recent years due to the sufficient photon harvesting of the blend photoactive layer including three absorption‐complementary materials. With the rapid development of highly efficient ternary OSCs in photovoltaics, the precise energy‐level alignment of the three active components within ternary OSC devices should be taken into account. The machine‐learning technique is a computational method that can effectively learn from previous historical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 38 publications
0
66
0
Order By: Relevance
“…At first, the 121 V oc data points were collected as an available dataset from recently reported review articles . A total of 121 fullerene derivative‐based ternary OSCs (26 polymer donors and 90 third components) were trained in the study.…”
Section: Methodsmentioning
confidence: 99%
“…At first, the 121 V oc data points were collected as an available dataset from recently reported review articles . A total of 121 fullerene derivative‐based ternary OSCs (26 polymer donors and 90 third components) were trained in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Some ML approaches have been introduced into the OSCs for the screening of complex molecules and their PCE prediction of relevant photovoltaic systems [33][34][35][36][37][38][39][40] . For instance, Sun et al 33 developed a deep learning model based on a convolutional neural network (CNN) that enables recognition of chemical structures and automatic classification for predicting the PCE of D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Shinji et al reported a screening of conjugated molecules for polymer-fullerene OSC applications with artificial neural network (ANN) and random forest (RF) algorithms by importing parameters such as PCE, molecular weight, energy levels, and electronic properties with digitized chemical structures 36 . However, these examples of the application of ML algorithms were mostly used in the fullerene-based OSCs, whereas the reports about the application of ML algorithms in the non-fullerene-based OSCs are limited [41][42][43] . As non-fullerene acceptors (NFAs) draw researchers' attention and have become research hotspots [44][45][46] , and most state of art OSCs with efficiency up to 13-17% were achieved by NFA OSCs in these few years 4,47,48 , we shoud pay more attention to the applications of ML approaches that would tackle broader and more complex non-fullerene OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the lower accuracy of the XGB model when predicting 20 new validation experiments may be due to insufficient generalization of the developed XGB model which is more or less influenced by a few potential exceptions (e.g., rare items in a majority of data). [45][46] Nevertheless, we believe that as the first proof-of-concept for predicting the crystallization propensity of MONCs the XGB model shows great potentials in guiding chemists, especially new entrants, to screen the reaction parameters for synthesizing new MONCs single-crystal.…”
Section: Resultsmentioning
confidence: 99%